Al-Kifāḥ min ajli dawlah Islāmīyah ‘abra al-masār al-dīmuqrātī: Tajribat al-Ḥizb al-Islāmī al-Mālizī (PAS) - Helmy, Muhammad Irfan; Nurdin, Ahmad Ali (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2020)
This paper discusses how PAS follows democratic way to achive its political goal to establish an Islamic state. Is it true that the establishment of PAS was triggered by its motive to struggle for Islamic state which is not addressed by UMNO? What and how is the concept of Islamic state according to PAS? How and to what extent did Muslim and non-Muslim in Malaysia accept PAS idea, in Malaysian election history, particularly in the last 2018 election? By analysing document of PAS Islamic state, party’s statute, and PAS performance from election to election, the researcher argues that up to present PAS was unsuccessfull to reach its political goal yet. PAS only won and occupied Kelantan and several times won in Sabah and Terengganu. The result of 2018 election shows that PAS was beaten by Pakatan Harapan coallition as well as Barisan Nasional coalition. However, PAS’s struggle through democratic way has significantly contributed to reduce a negative image of Islamic movement in South East Asia. Islam is not monolithic and Islam is compatible with democracy. PAS’s struggle is a clear proof.